Influence of graded levels of N, P, K on growth, yield and economics of hybrid rice cultivars (Oryza sativa) under subtropical irrigated conditions - Kumar, Sanjeev; Bazaya, B.R.; Sharma, Ashu; Puniya, R.; Bhagat, Sapna (Annals of Agricultural Research, 2017)
A field experiment was conducted during kharif season of 2014 to study the influence of gradedlevels of N, P, K on growth, yield and economics of hybrid rice cultivars under sub-tropical irrigatedconditions. Among hybrids, PHB-71 recorded significantly higher plant height, dry matteraccumulation, number of panicles/m2, number of grains/panicle, 1000-grain weight, grain yieldand straw yield. Application of N120:P60:K30 kg/ha and N150:P75:K38 kg/ha produced significantlyhigher plant height, dry matter accumulation, number of panicles/m2, number of grains/panicle,1000-grain weight, grain yield and straw yield than N60:P30:K15 kg/ha and N90P45K23 kg/ha. Thehighest net returns (Rs 83514) and benefit: cost ratio (2.59) was recorded with PHB-71 followed byDRRH-3 (2.19). However, the highest net returns (Rs 78379) was obtained with N150P75K38 kg/hafollowed by N120P60K30 kg/ha level whereas the B:C ratio (2.36) was higher in N120P60K30 kg/ha.